Consumer Preferences Of Soybean Processed Commodities In Semarang City - Ikhwanudin Ikhwanudin; Sri Wahyuningsih; Lutfi Aris Sasongko (MEDIAGRO, 2010)
Health is influenced by the quality of consumed food every day. Sothat people become healthy, strength, and have normal growth, consumedfood have to fulfill fundamental element which required by body (nutrition& calorie), consist of protein, fat, carbohydrate, vitamin, and mineral. Oneof its alternative is to consume food which contain legume like soy,because soy have complete content element of nutrition. Tofu and mouldedsoya bean is made food type of soy. This research aim to to know : ( 1) Dotofu and moulded soya bean become the most choosen food in Semarangcity; ( 2) To know factors influencing consumer in chosening tofu andmoulded soya bean and ( 3) To know the alternative for tofu and mouldedsoya bean. Basic method that is used is descriptive method analysis andenforcement method that is used is method of survey. Method intake of areasampel and responder is purposive sampling. used data in the form ofprimary data and sekunder collected through interview with kuesioner,record-keeping, documentation and observation in the form of photo.Responder characteristic of tofu and moulded soya bean is woman agebetween 41 until 45 year, with merried status. Most work of responder isemploying at other sector and level education of responder is ElementarySchool. Earnings from most responder is Rp 1.000.000,- up to Rp.1.500.000, with amount of responsibility counted 3 up to 4 people. Budgetfor food is Rp. 250.000,- up to Rp. 300.000,- each month. Tofu andmoulded soya bean become most taken food because its price and itsalternative is egg. Pursuant to appetite to tofu and of moulded soya beanconsumer like to medium size of white tahu and wrapped plastic tempe withmedium size, consumer the get information about tahu and tempe as foodwhich good to consumed from environment. Tofu and moulded soya bean isthe most consumed food with storey level often in a week, and consumerexpressed their satisfaction. The most favourite type of processing tofu isfried tofu and moulded soya bean processing favourite is fried moulded soyabean.